2022
DOI: 10.21608/aadj.2022.267266
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Nano-Fillers Addition on The Mechanical Properties of Heat-Polymerized Acrylic Resin

Abstract: Aim: To evaluate flexural strength (FS) and micro-hardness of poly(methylmethacrylate) (PMMA) denture base material modified with Zirconium oxide (ZrO2), titanium oxide (TiO2) and zinc oxide (ZnO) nanoparticles powder with different concentration (1.5, 3 and 5% ) Subjects and Methods: Test specimens of PMMA of dimensions (65 ×10 × 2.5 mm) were made from heat-cured acrylic resin served as control group Another nine group were made of PMMA containing 1.5, 3, and 5% (w/w) (ZrO2), ( TiO2) and (ZnO) nanoparticles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous study found that adding aluminum oxide to the Polymethylmeth acrylate (PMMA) denture base resin enhances flexural strength [18]. There were substantial variations in flexural strength between hot-cure acrylic resin testing groups, according to the null hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…Previous study found that adding aluminum oxide to the Polymethylmeth acrylate (PMMA) denture base resin enhances flexural strength [18]. There were substantial variations in flexural strength between hot-cure acrylic resin testing groups, according to the null hypothesis.…”
Section: Discussionmentioning
confidence: 97%